Excitement and prey: Captains' wives and the experience of marine animals on US whaling ships in the nineteenth century - Syväsalmi Emilia (Sage, 2025)
Captains' wives, who travelled with their husbands on US whaling ships in the middle of the nineteenth century, encountered marine animals during their journeys. Marine animals are often forgotten when writing animal histories. However, they are a visible theme in the wives' journals, which are the main source for this article. The author argues that marine animals created a shared experience for the wives, the ship's crew and the officers. It was because of these interspecies encounters that the wives became part of the ship's society. A second argument concerns the contradictory relationship that the captains' wives had with the marine animals: on the one hand, they were merely seen as a resource; on the other, they were sources of wonder. In this study, animal history becomes visible through the eyes of exceptional Victorian women who were facing a new environment at sea.